2015
DOI: 10.1177/1082013215583149
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, physical and sensorial evaluation of cookies supplemented with dairy powders

Abstract: The effect of dairy powders (skim milk powder, butter milk powder, sodium caseinate, yoghurt powder, milk powder and colostrum powder) on cookie quality was studied. Cookies were tested for aw, calorimetric energy, diameter, thickness, spread ratio, breaking strength, colour, dough consistency and sensory evaluation. The lowest aw values were obtained for cookies containing colostrum powder; also the highest calorimetric energy values were obtained from the colostrum powder-added cookies. Diameter values of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In fact, a negative correlation between spread ratio and hardness was obtained in this study (r = À0.8681, P < 0.01). This inverse correlation was also observed by Singh & Mohamed (2007), Sert et al (2016) and Yadav et al (2011) in different proteinenriched cookies.…”
Section: Texturesupporting
confidence: 65%
See 1 more Smart Citation
“…In fact, a negative correlation between spread ratio and hardness was obtained in this study (r = À0.8681, P < 0.01). This inverse correlation was also observed by Singh & Mohamed (2007), Sert et al (2016) and Yadav et al (2011) in different proteinenriched cookies.…”
Section: Texturesupporting
confidence: 65%
“…This inverse correlation was also observed by Singh & Mohamed (), Sert et al . () and Yadav et al . () in different protein‐enriched cookies.…”
Section: Resultsmentioning
confidence: 87%
“…The highest bread volume was obtained with the colostrum powder addition. Colostrum powder has lower lactose content and higher fat and ash content than BMP, SMP and YP (Sert et al, 2016). Colostrum powder with high mineral content positively affected bread yeast activity compared to other powders.…”
Section: Bread Propertiesmentioning
confidence: 97%
“…Additionally, caseins exhibit interesting techno-functional properties due to their amphiphilic character. This characteristic enables them to act as surfactants, emulsifiers, thickeners, and foaming and water-binding agents in flour doughs [13]. A casein hydrolysate (CH) is even more suitable than whole caseins because its solubility is increased and the allergic reactions are prevented, while maintaining the nutritional value and some of the functional properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the addition of 5-10% sodium caseinate (NaCas) reduced the dough hardness [17]. In contrast, Sert et al (2016) [13], reported a significantly higher dough consistency upon NaCas addition.…”
Section: Introductionmentioning
confidence: 99%